Pengaruh Pola Komunikasi Dan Kecerdasan Emosional Orang Tua Terhadap Akhlak Remaja - Sahriani Hasibuan; Muhammad Darwis Dasopang (Studi Multidisipliner: Jurnal Kajian Keislaman, 2019)
The purpose of this study is to test the theory which is then analyzed again into a new finding. This type of research is quantitative with a collaborative method obtained from a questionnaire. The results of this study indicate that the pattern of parental communication (X1) towards adolescent morals (Y) has a correlation of 0.890 or 89% showing a very strong relationship. The correlation of emotional intelligence of parents (X2) with the morals of adolescents (Y) has a value of 0.926 or 92% indicating a very strong relationship. Whereas to test the significance level of F 5%, the effect of parental communication patterns on adolescent behavior shows that Fh (270,761) Ft (0,000) shows an appropriate and acceptable relationship.